KAJIAN YURIDIS PELAKSANAAN PENGALIHAN KREDIT DARI DEBITUR LAMA KEPADA DEBITUR BARU TERHADAP KREDIT MODAL KERJA PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. CABANG CIK DI TIRO YOGYAKARTA - , DWI YULI CHRISNAWATIE, Ninik Darmini, SH., M. Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was intended to identify factors causing novation from old debtor to new debtor on working capital credit in Bank Rakyat Indonesia (Persero), Cik Di Tiro Yogyakarta Branch and to study legal protection for creditor over notation from old debtor to new debtor on working capital credit without bank knowing. It is juridical empirical research. It was done through direct interview with respondent and completed with secondary data. Sample was taken using non probability sampling with purposive sampling technique to select sample. Data analysis was done using qualitative approach. Data analysis was presented descriptively. The result indicated that factors causing novation from old debtor to new debtor over working capital credit in PT Bank Rakyat Indonesia (Persero) Tbk, Cik Di Tiro Yogyakarta Branch is (a) change in legal business entity from CV to PT and (b) debtor died or replacement of debtor position due to the debtor died. Legal protection for creditor on novation from old debtor to new debtor on working capital credit done without bank knowing was done with two methods. First, preventive legal protection is done using clause and stipulation in working capital creditand credit supervision and debtor assistance by visiting directly to debtor business periodically once three months during credit period. Second, repressive legal protection was done by doing provision that regulate authority of bank to terminate credit agreement and can collect unpaid loan and its interest immediately and in cash and to execute credit collateral of encumbrance.